Od teorii do hermeneutyki. Przypadek Stanisława Balbusa - Sobolczyk, Piotr (Wydawnictwo Naukowe UAM, 2006)
The article presents Stanisław Balbus, one of the most influential Polish literary theorists. Balbus (somehow like Barthes) began as a structuralist, but also practiced literary criticism of the interpretive mode, however later, during the time of the paradigm change in Poland, he evolved to the hermeneutics and to the interpretive paradigm. His case may be seen as typical, as one of a few ways of reacting towards a paradigm change. The author uses discourse analysis methods as well as a narrativist-constructivist methodology, and reads three books of Balbus: Między stylami (Between styles), Poezja w czasie marnym (Poetry in the weak time - about Tadeusz Nowak) and Świat ze wszystkich stron świata (The world from all the sides of the world - about Wisława Szymborska).
From theory to hermeneutics. Stanisław Balbus' case